Identifying Challenges in Arabic Language Learning at Madrasah Aliyah and Teachers’ Strategies to Overcome Them: A Descriptive Qualitative Study - Ajcwa April Adil; Muthia Rania Sofyan; Radja Azhar Ismail (Gunung Djati Conference Series, 2026)
This study aims to identify the challenges faced by teachers in the process of teaching Arabic at Madrasah Aliyah, the obstacles experienced by students in learning Arabic, the strategies applied by teachers to address these challenges, and the effectiveness of these strategies in overcoming difficulties in Arabic language learning. The research employs a descriptive qualitative approach to provide an in-depth understanding of the challenges and instructional strategies in Arabic language learning at Madrasah Aliyah. Primary data were obtained from teachers, students, and school personnel, while secondary data were drawn from instructional documents. Data were collected through interviews, observations, and documentation using a triangulated procedure. Data analysis followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, resulting in accurate, contextual, and credible findings. The research reveals that Arabic language learning at Madrasah Aliyah faces multidimensional challenges, such as students’ low linguistic competence, limited facilities, insufficient methodological variety, low motivation, and minimal language exposure. Linguistic, psychological, and methodological barriers mutually reinforce students’ learning difficulties. To address these issues, teachers implement strategies focusing on language reinforcement, method variation, motivation enhancement, and the use of instructional media. Communicative strategies, vocabulary enrichment, positive reinforcement, and audiovisual media are found to be the most effective. Learning outcomes can be optimized when these strategies are applied consistently with adequate facility support and ongoing teacher training.